Strategi Penerapan Total Quality Management (TQM) Berbasis Biaya Mutu di RSUD Kota Mataram: Strategy for Implementing Total Quality Management (TQM) Based on Quality Costs in Mataram City Regional Hospital - Delima Khafila Fatikasari; Halpiah; Baiq Dewi Lita Andiana (Pinus Publishing, 2025)
In terms of economic accounting, the quality costs incurred by a company are quite high, namely around 20% of its revenue. This means that the Mataram City Regional Hospital incurs an annual quality fee of around Rp. 1,160,000,000/year to be allocated to finance further education for 11 doctors, training for 36 medical personnel and 5 non-medical personnel. The management team of Directors is 6 people. From a total of 1,210 human resources. This research uses a qualitative method with a narrative approach, which aims to find out whether Total Quality Management has been implemented well in accordance with TQM principles, what the TQM implementation strategy is, and whether the budgeted costs are in accordance with the quality targets of the Mataram City Regional Hospital management. Based on the results of research and discussion regarding the Strategy for implementing Total Quality Management (TQM) based on quality costs at the Mataram City Regional Hospital, it can be concluded that the Mataram City Regional Hospital applies TQM in aspects of patient service, organizational design, operational principles and human resource development, quality principles and processes, accounting principles. control and capacity and marketing.